Technology and application of long directional drilling hydraulic fracturing for preventing rock burst in thick and hard roof - Shankun ZHAO; Bingqin WANG; Zhenguo SU; Shaogang LI; Yue SHI; Xincheng SANG; An LIU; Weige HAN (Meikuang Anquan)
With the extensive development of coal resources in Shaanxi and Mongolia, rock burst phenomenon has gradually become an important problem affecting the safety production of coal mines. Aiming at the problem of uniform pressure relief of hard thick roof of rock burst coal seam, taking 23301 working face of a mine as the engineering background, ABAQUS numerical simulation software is used to simulate the hydraulic fracturing process of directional long drilling. The numerical simulation results show that the fractures mainly expand in the direction of perforation, and there is a dense fracture network around the fractured layer, and a single main fracture tends to form with the increase of the expansion radius, which proves that the fracturing operation can effectively achieve the purpose of roof pressure relief. The target strata were determined according to the theory of key strata and a high-low layout scheme was designed for the roof. The fracturing effect was discussed by focusing on the results of holes 2-1. The application results show that the fractures are mainly horizontal and the fracture network is complex. During fracturing, the injection pressure curve fluctuates zigzag in the fracture expansion zone and the expansion is fully and continuously. Fracturing operation significantly reduces the roadway deformation during mining, realizes the safe and efficient mining of the working face.